Современные методы кодирования речевого сигнала - Бондаренко, М. Ф.; Работягов, А. В.; Щепковский, С. В. (ХНУРЭ, 2008)
В статье проведен обзорный анализ современного состояния исследований в области кодирования речевого сигнала. Рассмотрены основные применяемые и перспективные методы кодирования.The modern methods of encoding of speech signal are analysed.Methods, already having status of international standards,and also perspective methods which are in the stage of introduction development, are considered. As a result of the conducted research a conclusion is done about possibility of creation in the near time methods with more high degree of compression of speech.